Open-Circuit Fault Diagnosis and Fault-Tolerant Strategies for Full-Bridge DC-DC Converters - Pei, Xuejun; Nie, Songsong; Chen, Yu; Kang, Yong (IEEE transactions on power electronics, 2012)
This paper proposes a four-step open-circuit fault diagnosis and fault-tolerant scheme for isolated phase-shifted full-bridge (PSFB) dc-dc converters to improve the reliability. The fault diagnostic method utilizes the primary voltage of the transformer as the diagnostic criterion, which can be obtained easily by adding an auxiliary winding. When an open-circuit fault occurs in any switch of the PSFB converter, the proposed fault detection method can generate an indication of the abnormal state and trigger an active-phase-shifted in the control system. Under the APS state, it is very easy to locate the exact position of faulty switch because the voltage waveform of the primary winding heavily depends on the location of the faulty switch. After locating the position of the faulty switch, the PSFB converter is reconfigured into an asymmetrical half-bridge (AHB) converter by turning ON the normal switch in the faulty leg and adding a redundant winding to the secondary side. Therefore, the rebuilt AHB converter can keep the output voltage constant under a reduced power rating after the open-circuit fault. The operational principle, design consideration, and implementation are discussed in this paper. The experimental results are given to verify the validity of theoretical analysis. The proposed strategies outperform the traditional schemes in terms of cost, reliability, and power density.